An Empirical Study Of Productivity Growth In EU28 - Spatial Panel Analysis - Olejnik, Alicja (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper investigates the spatial process of productivity growth in the European Union on the foundations of the theory of New Economic Geography. The proposed model is based on the study of NUTS 2 regions and takes into consideration a spatial weights matrix in order to better describe the structure of spatial dependence between EU regions. Furthermore, our paper attempts to investigate the applicability of some new approaches to spatial modelling including parameterization of the spatial weights matrix. Our study presents an application of the spatial panel model with fixed effects to Fingleton’s theoretical framework. We suggest that the applied approach constitutes an innovation to spatial econometric studies providing additional information hence, a deeper analysis of the investigated problem.